Time-restricted feeding affects colonic nutrient substrates and modulates the diurnal fluctuation of microbiota in pigs - Wang, Hongyu; Li, Qiuke; Xu, Rongying; Su, Yong; Zhu, Weiyun (Frontiers in Microbiology, 2023)
Studies have demonstrated that time-restricted feeding (TRF) can regulate gut microbiota composition. However, it is unclear whether TRF could affect the gut microbial rhythmicity in growing pigs. Therefore, the present study aimed to explore the effects of TRF on the dynamic fluctuation of the gut microbiota. A total of 10 healthy growing pigs equipped with T cannula were employed. Pigs were randomly allotted to the free access (FA) and the TRF groups with 5 replicates (1 pig/replicates). Pigs in the FA group were fed free access during the whole experimental period, whereas pigs in the TRF group were fed free access three times per day within limited times (7:00~8:00, 12:00~13:00, 17:00~18:00). The experiment lasted for 15d, at 06:00 am of the d 16, colonic digesta were collected at a 6-hour interval for consecutive 24 h marked as T06 (06:00), T12 (12:00), T18 (18:00), T24 (24:00), T30 (06:00) respectively. Results showed that TRF altered the distribution of feed intake without changing the total feed intake within a day (P = 0.870). TRF decreased the overall concentration of colonic cellulose and altered their oscillating patterns. All alpha-diversity indexes of different time points showed significant differences regardless of feeding pattern with a trough at T18 or T24. TRF shifted the trough of the alpha-diversity index Simpson and Invsimpson. TRF lost the rhythmicity of Prevotellaceae, Ruminococcaceae, Bacteroidales_S24-7_group, and Peptococcaceae and gained the rhythmicity of Pasteurellaceae, Clostridiaceae_1, Veillonellaceae, and Peptostreptococcaceae. Also, TRF altered the interaction pattern by increasing the microbes involved in the co-occurrence network and their crosstalk, especially at T24. Interestingly, the microbial variation at T24 could largely explained by the colonic substrates starch (R2 = 0.369; P = 0.001), cellulose (R2 = 0.235; P = 0.009) and NH4-N (R2 = 0.489; P = 0.001). In conclusion, TRF has changed the concentrates of cellulose and the relative abundance of specific microbes and certain microbial metabolites. In addition, TRF has more powerful effects on the fluctuation modes of these nutrient substrates, microbes, and metabolites by shifting their peaks or troughs. This knowledge facilitates the development of precision regulation targeting gut microbial rhythmicity.